Functional outcome of anterior cruciate ligament reconstruction in Nepalese females: A prospective observational study - Bhattachan, Sijan; Bhujel, Bijay; Hamal, Bhadra; Khanal, Sudeep; Sherchan, Binod (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: The increased risk of Anterior Cruciate Ligament (ACL) injury in the female population is multifactorial. Arthroscopic ACL reconstruction using hamstring autograft is an established and widely practiced surgery for the ACL-injured knee. The purpose of this study was to evaluate the functional outcome of anatomic single-bundle anterior cruciate ligament reconstruction using hamstring and peroneus longus autograft in Nepalese female patients. Methods: This was a prospective observational study of 35 female patients with ACL injuries who underwent arthroscopic ACL reconstruction using hamstring and peroneus longus autografts, as per the surgeon’s convenience, at the National Trauma Center, NAMS, from June 2024 to May 2025. Functional outcomes were assessed using the Tegner Lysholm score. Results: The Mean age of the patient was 37.9 years. The most common mode of injury was a fall injury. A hamstring graft was used in 25.7% of patients, and the graft size was 8 mm in all cases. The peroneus longus graft was used in 74.28% of cases, and the size of the graft ranged from 8 to 9 mm, with a mean size of 8.33mm. The mean preoperative Tegner Lysholm score was 60.76 ± 1.23, and the postoperative score at 6 months was 91 ± 2.43 (p=0.0001). Fourteen (40%) patients had an excellent outcome, and 21 (60%) had a good result. Conclusion: Arthroscopic anatomic anterior cruciate ligament reconstruction using hamstring autograft and peroneus longus is an effective method for ACL reconstruction in female patients with ACL injury and gives an excellent to good functional outcome.